2019
DOI: 10.3390/jcm8101594
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Outcomes and Quality of Care in Children with Sickle Cell Disease Diagnosed by Newborn Screening: A Real-World Nation-Wide Study in France

Abstract: This study’s objective was to assess, on a national scale, residual risks of death, major disease-related events, and quality of care during the first five years in children diagnosed at birth with sickle cell disease (SCD). Data were retrospectively collected from medical files of all children with SCD born between 2006–2010 in France. Out of 1792 eligible subjects, 1620 patients (71.8% SS or S/beta°-thalassemia -SB°-) had available follow-up data, across 69 centers. Overall probability of survival by five ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 23 publications
1
18
3
Order By: Relevance
“…Because of the difference in VOC definition, it is not surprising to see a higher overall VOC rate in patients aged 0-5 years in this study (59.5% of the total cohort) than in the French study. RBC transfusion was also the most often used therapeutic intervention by 3 and 5 years among all patients in the analysis by Brousse et al [25], similar to trends observed in this study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Because of the difference in VOC definition, it is not surprising to see a higher overall VOC rate in patients aged 0-5 years in this study (59.5% of the total cohort) than in the French study. RBC transfusion was also the most often used therapeutic intervention by 3 and 5 years among all patients in the analysis by Brousse et al [25], similar to trends observed in this study.…”
Section: Discussionsupporting
confidence: 90%
“…It has been shown that as patients with sickle cell disease age, the VOC rate and other disease complications tend to progressively increase. Another study conducted in France [25] following sickle cell disease patients up to the age of 5 years old noted that 42.9% of their cohort experienced a first VOC at 3 years, a lower rate than observed in the 0-3 years age group in this study. The French study defined VOC as pain and dactylitis, rather than a composite of VOC and ACS as in this study.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Sickle cell disease (SCD) is an increasing genetic hemoglobinopathy in France, with a persistent high morbidity among children [1]. Vaso-occlusive episodes (VOEs), also known as acute severe pain episodes, are the leading cause of hospitalization among children with SCD [1].…”
Section: Introductionmentioning
confidence: 99%
“…Sickle cell disease (SCD) is an increasing genetic hemoglobinopathy in France, with a persistent high morbidity among children [1]. Vaso-occlusive episodes (VOEs), also known as acute severe pain episodes, are the leading cause of hospitalization among children with SCD [1]. In children admitted for VOE, the main severe complication is the secondary development of acute chest syndrome (ACS), an acute clinical condition of SCD defined by fever and/or respiratory symptoms and accompanied by new pulmonary infiltrate on a chest X-ray [2].…”
Section: Introductionmentioning
confidence: 99%